KETERKAITAN TRANSDISIPLINARITAS DENGAN KEUNGGULAN BERSAING SERTA FUNGSI MEDIASI ADAPTABILITAS ORGANISASI - Sugito, Pudjo; ., Kamaludin (Buletin Studi Ekonomi; VOL.22.NO.1. FEBRUARI 2017 (PP 1-112), 2017)
The goal of this research is to analysze the effect of transdiciplanarity toward competitive advantage and role of organizational adaptability mediation. The research population are small and medium industries at Malang. Data collection techniques use proportional random sampling. The number of respondents in this study determined the 200 respondents who are performing well, as a minimum requirement that is needed in data analysis techniques Structural Equation Model (SEM). Further, it will be used two kinds of analysis techniques (a) factor analysis, is used to confirm the factors most dominant variable in one group and (b) regression weight in SEM, used for confirmatory examine how much the relationship between variables. Based on the results of data analysis revealed that transdisiplinarity significantly effect toward competitive advantage, and organizational adaptability plays an important role to that linkages.